The Mediating Role of Job Dedication in The Relationship Between Participative Leadership and Achieving High Performance in Higher Education Institutions - Nadhum Jawad, Saja; Ali Neamahr , Marwa; jabber jahil, Alaa; Ziad Mohammed, Ehab (Iraqi Journal for Administrative Sciences, 2026)
This research aims to identify the impact of participative leadership on achieving high organizational performance through the mediating role of organizational commitment, with application at the College of Administration and Economics, University of Karbala. The researchers adopted dimensions of participative leadership (decision-making participation, human relations, and information building), dimensions of job dedication (conscientiousness, goal orientation, and general expectation of task success), and dimensions of high performance (management quality, long-term commitment, openness and effective orientation, continuous improvement, and workforce quality). The study sample included 100 employees and faculty members, and data were collected through questionnaires and interviews. Statistical tools such as Pearson correlation (SPSS V.25) and structural equation modeling (AMOS V.23) were used for data analysis. The findings revealed that job dedication plays a significant mediating role in strengthening the relationship between participative leadership and achieving high performance.